2014
DOI: 10.1364/oe.22.025517
|View full text |Cite
|
Sign up to set email alerts
|

Combined holography and thermography in a single sensor through image-plane holography at thermal infrared wavelengths

Abstract: Holographic interferometry in the thermal wavelengths range, combining a CO 2 laser and digital hologram recording with a microbolometer array based camera, allows simultaneously capturing temperature and surface shape information about objects. This is due to the fact that the holograms are affected by the thermal background emitted by objects at room temperature. We explain the setup and the processing of data which allows decoupling the two types of information. This natural data fusion can be advantageousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In particular defect on column C2 is much better seen than with thermography. This shows that complementarity of these NDI techniques should be envisaged for future works, with separate techniques or under integrated schemes [10,11].…”
Section: Discussion-conclusionmentioning
confidence: 95%
“…In particular defect on column C2 is much better seen than with thermography. This shows that complementarity of these NDI techniques should be envisaged for future works, with separate techniques or under integrated schemes [10,11].…”
Section: Discussion-conclusionmentioning
confidence: 95%
“…The CAD model of the instrument (left) and the realized instrument (right). (Chen, 2014;Chen et al, 2014) n u m b e r 5 • 7 shearographic inspection (Georges et al, 2014). The integrated IR camera enabled researchers to map the surface temperature of the painting throughout the process.…”
Section: Test Setupmentioning
confidence: 99%
“…This project also led to the development of a fringe database for using fringe patterns unique to each work as a method of authentication. Previous work (Georges et al, 2014) incorporating thermography, holography, and shearography has also indicated a multidomain approach to fault detection in complex multimaterial, multilayered objects with structural and mechanical complexity similar to that of paintings.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is a LWIR speckle interferometer combining a CO 2 laser with a thermal imaging device. 15 It is a possibility that can be of interest for vibration analysis and will be discussed in the paper. The second one is shearography in the visible (VIS), which is also well suited for out-of-laboratory applications because of its inherent self-referenced configuration.…”
Section: Introductionmentioning
confidence: 99%